Altered degree centrality in patients with non-neuropsychiatric systemic lupus erythematosus: a resting-state fMRI study. (19th January 2022) - Li, Xiaolou; Zhang, Peng; Zhou, Wensu; Li, Yuan; Sun, Zhongru; Chen, Jinhua; Xia, Jianguo; Zou, Hongmei
Abstract : This study used a voxel-wise degree centrality (DC) method to evaluate differences in brain activity between patients with non-neuropsychiatric systemic lupus erythematosus (non-NP-SLE) and healthy controls (HCs) and to assess the relationship of DC values with clinical and neuropsychological data. Thirty-two female patients with non-NP-SLE and 28 well-matched HCs were recruited and underwent resting-state functional MRI. Differences in spontaneous brain activity between the two groups were evaluated using a DC method. Correlations between the altered DC values of specific brain regions and clinical and neuropsychological data were explored using Spearman correlation analysis. Receiver operating characteristics curve analysis was applied to differences in DC values in specific brain regions to determine their value in distinguishing patients with non-NP-SLE from HCs. Compared with HCs, DC values in patients with non-NP-SLE were significantly lower in the bilateral postcentral gyrus and the orbital part of the left superior frontal gyrus (LFMO). DC values in some specific brain regions such as the bilateral postcentral gyrus and the LFMO correlated with Mini-Mental State Examination scores in both subject groups. In patients with non-NP-SLE, DC values of the right postcentral gyrus were positively correlated with IgA levels, and DC values of the LFMO were positively correlated with Systemic Lupus Erythematosus Disease Activity Index 2000 scores, as well as IgA levels. Receiver operating characteristics curve analysis revealed that the DC values of specific brain regions can be used to differentiate patients with non-NP-SLE from HCs.